Design of automatic gate mechanism - Chai, Fook Siang (2009)
Automatic gate is one of the most preferable domestic intended to provide easy access to gated home. There are three types of automatic gate mechanism, such as sliding, screw drive piston and swing cubic underground. Designs available today are limited only to the three types mentioned. Products available in the market are quite pricy, even when installation and maintenance cost is not yet been considered. Most of the products available in our country are imported from foreign country. The objectives of this project is to study, analyze, and develop a new mechanism that concern with the cost reduction and the mechanism produce should be safe and reliable as well. Here, different type of analysis method was in used in order to develop a proper automatic gate mechanism. Those methods are finite element modeling and mechanical design concept and theories. Stress analysis is done by applying variable maximum loaded stress to ensure the product life service is sustainable. Analysis done also helps in order to select proper material and component specification or sizes for the product development. Therefore, the durability assessment results are significant to reduced the cost and improve the product reliability so as to gain customer confidence. In order to improve the designed mechanism, vibration factor should be take into consideration and more features should be provided.